An Approach to the Welfare Analysis of Inter-Temporal Resource Alloca¬tion by Jerome Rothenberg, (Lecture Series No. 22). Athens: Center of Planning and Economic Research, 1967. pp.75. (The Pakistan Development Review, 1967)
Rothenberg's book contains three lectures read at the Center of Planning and Economic Research in Athens. The author starts by arguing that the problem of welfare comparisons over considerable time intervals is simply that the populations being compared in the two periods are not unchanged. The normative criteria economists usually use for making welfare comparisons an unchanging population, i.e., each individual must be present in the various situa¬tions that are compared. The author, by contrast, intends to examine situations where only some individuals are present in one of the two situations com¬pared. His treatment of the linkage between two situations over time is based on two key assumptions: i) the population composition changes almost conti¬nuously, ii) the new additions to the population are familiarly linked to the exist¬ing members. The author concludes that under certain simplifying assumptions— e.g., that the utility function of each individual remains unchanged through life and that parents act on behalf of their heirs—no important problem of intergenerational comparability arises except where intertemporal externalities are involved.